A direct numerical simulation method for solid-solid collision and coupling with fluid. (7th March 2023) - Yang, Ming; Liu, Jubao; Ding, Yuqi; Yue, Qianbei; Zhang, Qiang
Abstract: The collision between solids in fluid is common in engineering, but the numerical simulation method is less studied. A direct numerical simulation method combining the sharp interface immersed boundary method and the finite element method based on penalty function was established for solid–solid collision and coupling with fluid. The lubrication model for cylinder structures with and without fluid flow was developed using the data regression method. The partitioned coupling algorithm was used to realize the coupling solution between the fluid and solid domains. Four numerical examples were presented to demonstrate the validity of the established method. The numerical simulation of the vortex-induced collisions between two side-by-side cylinders showed the capabilities of the proposed method.